African nationalism - Noyberger, Binyamin (Routledge studies in nationalism and ethnicity, 2023)
Introduction -- Africans, African Americans, and the Roots of Pan-African Nationalism -- From Pan-Negroism to Territorial Nationalism: Nationalism without Nations -- Négritude -- Continental Pan-Africanism -- The New Nationalism and its Historical Heritage -- The Permeation of Western Liberal Concepts -- Socialist and Communist Concepts and Anticolonial African Nationalism -- Radical Ideologies of National, Economic, Social, and Cultural Liberation -- Opponents of National Independence -- The Organization of African Unity and the African Union -- Black Zionism: The Return to Africa in Theory and Practice -- Conclusion -- Appendix 1: Albert Memmi -- Appendix 2: Alioune Diop -- Appendix 3: Frantz Fanon -- Appendix 4: Julius Nyerere.